2015
DOI: 10.1089/mab.2014.0081
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of Neutralizing Monoclonal Antibodies Against the S1 Subunit Protein of QX-like Avian Infectious Bronchitis Virus Strain Sczy3

Abstract: Infectious bronchitis (IB) is a highly contagious disease in chickens caused by infectious bronchitis virus (IBV). The present study was carried out with the aim to develop anti-spike 1 (S1) subunit monoclonal antibodies (MAbs) that could react with IBV strains of different genotypes. The high antigenicity region of S1 gene of an QX-like IBV strain Sczy3 was amplified and ligated into the prokaryotic expression vector pET-32a(+), and the recombinant His-S1 fusion proteins were expressed and purified. The purif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 36 publications
2
6
0
1
Order By: Relevance
“…That is, as a cofactor for the synthesis of immunoglobulins, C 0 3 convertase, immune cell adhesion, antibody-dependent cytolysis, IgM lymphocyte binding, macrophage response to lymphokines, and the adhesion of helper T lymphocytes (Tam et al, 2003). These data are in accordance with the results described above (Zou et al, 2015). These authors have demonstrated that this molecule promotes more antigenic and immunogenic power around this active site, giving an immune response of 100% neutralizing antibodies.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…That is, as a cofactor for the synthesis of immunoglobulins, C 0 3 convertase, immune cell adhesion, antibody-dependent cytolysis, IgM lymphocyte binding, macrophage response to lymphokines, and the adhesion of helper T lymphocytes (Tam et al, 2003). These data are in accordance with the results described above (Zou et al, 2015). These authors have demonstrated that this molecule promotes more antigenic and immunogenic power around this active site, giving an immune response of 100% neutralizing antibodies.…”
Section: Discussionsupporting
confidence: 87%
“…The S1 gene is now commonly used as a marker of the IBV classification. Although it is highly variable, it remains the first choice for the development of subunits of vaccines against IB (Zou et al, 2015). Furthermore, since there are still relatively conserved regions or epitopes in the S1 subunit, S1 could also be used as a targeted antigen in the development of diagnostic agents (Zou et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the available ELISA kits are designed to detect polyclonal antibodies against the whole virion and do not allow serotypization. Several alternatives to commercially available ELISA kits have been developed [ 52 , 53 , 54 , 55 , 56 ], some of which are based on serotype- or strain-specific monoclonal antibodies [ 57 , 58 , 59 ], but their use in routine diagnostics is currently limited.…”
Section: Approaches To Ibv Diagnosismentioning
confidence: 99%
“…A glicoproteína S possui segmentos S1 e S2, sendo que a porção S1 fica exposta no envelope viral, o que a torna um importante indutor da produção de anticorpos neutralizantes e, consequentemente, o principal alvo para o sistema imune do hospedeiro (CAVANAGH, 1983(CAVANAGH, , 2007. Devido a sua imunogenicidade, a proteína S1 pode ser um antígeno adequado para utilização em diagnóstico sorológico e monitoramento vacinal das aves (IGNJATOVIC; GALLI, 1994;ZOU et al, 2015).…”
Section: Palavras-chaveunclassified